2007
DOI: 10.1186/1476-069x-6-40
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor air pollution and emergency department visits for asthma among children and adults: A case-crossover study in northern Alberta, Canada

Abstract: Background: Recent studies have observed positive associations between outdoor air pollution and emergency department (ED) visits for asthma. However, few have examined the possible confounding influence of aeroallergens, or reported findings among very young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 67 publications
16
105
0
7
Order By: Relevance
“…Our tendency to find stronger associations during the warm season is consistent with previous findings (10)(11)(12)(13)(14)(15), and although we are unclear about the underlying mechanism for these apparent seasonal differences, it may simply be that during the warm season a greater proportion of asthma exacerbations are caused by air pollution. Rates of emergency department visits for pediatric asthma increase by 60% during the cold season; this increase is largely attributable to exacerbations triggered by viral infections.…”
Section: Table 4 Sensitivity Analyses: Rate Ratios and 95% Confidencsupporting
confidence: 82%
“…Our tendency to find stronger associations during the warm season is consistent with previous findings (10)(11)(12)(13)(14)(15), and although we are unclear about the underlying mechanism for these apparent seasonal differences, it may simply be that during the warm season a greater proportion of asthma exacerbations are caused by air pollution. Rates of emergency department visits for pediatric asthma increase by 60% during the cold season; this increase is largely attributable to exacerbations triggered by viral infections.…”
Section: Table 4 Sensitivity Analyses: Rate Ratios and 95% Confidencsupporting
confidence: 82%
“…1,2,[16][17][18][19] With specific regard to Windsor, Ontario, for 1 day lagged exposures in certain subgroups, Lavigne et al also reported statistically significant associations between ambient air pollution levels and emergency visits for asthma. 20 Exposure to ambient air pollution in Windsor increases the risk of ED visits for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Papers published since (or not considered in) the EPA's 2008 review also reported positive (though not always statistically significant) single-pollutant associations for hospital admissions and emergency room visits for: (a) asthma (Bell, Levy & Lin (2008), Colais et al, 2009;Giovannini et al, 2010;Halonen et al, 2008;Jalaludin et al, 2008;Samoli et al, 2011a;Szyszkowicz, 2008;Ueda, Nitta & Odajima, 2010;Villeneuve et al, 2007) and (b) respiratory causes (Colais et al, 2009;Eilstein et al, 2004;Faustini et al, 2013;Granados-Canal et al, 2005;Giovannini et al, 2010;Jayaraman & Nidhi, 2008;Thach et al, 2010;Vigotti et al, 2010).…”
Section: Mortalitymentioning
confidence: 99%
“…Where confounding by co-pollutants was assessed in the studies since the EPA (2008b) review, some robustness to adjustment was demonstrated for these respiratory health outcomes (Giovannini et al, 2010;Ueda, Nitta & Odajima, 2010;Halonen et al, 2008;Jalaludin et al, 2008;Jayaraman & Nidhi, 2008;Villeneuve et al, 2007). For example, Halonen et al (2008) found that NO 2 was a strong and independent predictor of asthma emergency room visits in children in Finland.…”
Section: Mortalitymentioning
confidence: 99%